2018
DOI: 10.1111/echo.13871
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of myocardial deformation in children, adolescents, and young adults exposed to anthracyclines: Systematic review and meta‐analysis

Abstract: There are significant abnormalities in GLS and GCS following anthracycline therapy acutely and late after treatment. The prognostic value of these strain abnormalities warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 57 publications
(279 reference statements)
1
15
0
1
Order By: Relevance
“…Unlike conventional LVSF and LVEF, which are limited to one plane, strain can be measured in three planes, providing a better determination of cardiac function. Previous studies provided evidence that strain abnormalities can be seen early despite preserved LVEF by conventional echo measures, identifying cardiac involvement in CCSs prior to the development of overt systolic dysfunction (43,(46)(47)(48)(49)(50)(51)(52)(53)(54). However, a more recent multicenter study of cardiac strain in a large cohort of pediatric CCSs found only mild differences in parameters of longitudinal strain between patients and healthy controls, with most CCSs (92.3%) having longitudinal strain values within the normal range.…”
Section: Speckle Tracking Imaging and 3d Echocardiographymentioning
confidence: 99%
“…Unlike conventional LVSF and LVEF, which are limited to one plane, strain can be measured in three planes, providing a better determination of cardiac function. Previous studies provided evidence that strain abnormalities can be seen early despite preserved LVEF by conventional echo measures, identifying cardiac involvement in CCSs prior to the development of overt systolic dysfunction (43,(46)(47)(48)(49)(50)(51)(52)(53)(54). However, a more recent multicenter study of cardiac strain in a large cohort of pediatric CCSs found only mild differences in parameters of longitudinal strain between patients and healthy controls, with most CCSs (92.3%) having longitudinal strain values within the normal range.…”
Section: Speckle Tracking Imaging and 3d Echocardiographymentioning
confidence: 99%
“…Advanced imaging modalities such as tissue characterization by cardiac magnetic resonance imaging 46,47 and echocardiography-derived myocardial deformation imaging (strain) have been used to detect subclinical cardiac dysfunction in populations at risk for heart failure (eg, after myocardial infarction). 48,49 When used in conjunction with blood biomarkers of cardiac injury and remodeling, these imaging biomarkers may be especially helpful for patients with cancer with borderline LV systolic function. To date, routine use of blood and imaging biomarkers in the asymptomatic oncology population remains limited primarily because of a lack of data to support improvement in cardiac and oncology outcomes.…”
Section: Undertake Appropriate Early Screening and Cardiovascular Manmentioning
confidence: 99%
“…[22][23][24][25] Besides gender, age remains to be another risk factor; people at extremes of ages are more susceptible to doxorubicin-induced cardiotoxicity. [26][27][28] Co-administration of other cardiotoxic drug, simultaneous mediastinal radiotherapy, and a large dose of doxorubicin can also increase the chance of developing doxorubicin-induced cardiotoxicity. 22 Presence of other comorbidities like hypertension, diabetes, co-existing cardiac disease, liver disease might increase the risk of doxorubicin-induced cardiotoxicity.…”
Section: Doxorubicin-induced Cardiotoxicitymentioning
confidence: 99%
“…29,30 The most severe cases of cardiotoxicity due to doxorubicin is seen in cancer survivors of the pediatric age group as this side effect usually do not become apparent years after stoppage of doxorubicin. 26 It has been estimated that around 60% of pediatric cancer patients receive anthracycline group of drugs and eventually 10% of them will develop doxorubicin-induced cardiotoxicity in the next 15 years. 31 Difference in onset of doxorubicin-induced cardiotoxicity has suggested that there might be different underlying molecular mechanism involved ( Table 1).…”
Section: Doxorubicin-induced Cardiotoxicitymentioning
confidence: 99%